2021
DOI: 10.3390/molecules26206282
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Assisted Protein to Creatinine Ratio Determination on a Single Paper-Based Analytical Device

Abstract: Proteinuria is a condition in which an excessive amount of protein is excreted in urine. It is, among others, an indicator of kidney disease or risk of cardiovascular disease. Rapid and reliable diagnosis and monitoring of proteinuria is of great importance for both patients and their physicians. For that reason, a paper-based sensor for proteinuria diagnosis was designed, optimized, and validated utilizing smartphone-assisted signal acquisition. In the first step, a few commonly employed protein assays were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…Few studies have evaluated the analytical performance of BPB assay in PADs but nevertheless, they are sufficient to make several comparisons. We achieved a LOD of 0.05 mg mL −1 ; it is comparable to the value of 0.039 mg mL −1 obtained by Lewinska and colleagues 10 and from 7-fold to 18-fold lower than the LOD detected in previous studies. 7,9 In terms of precision, our assay ranges from 3.2% to 8%, similarly to the values previously observed (2.6–6.4%).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Few studies have evaluated the analytical performance of BPB assay in PADs but nevertheless, they are sufficient to make several comparisons. We achieved a LOD of 0.05 mg mL −1 ; it is comparable to the value of 0.039 mg mL −1 obtained by Lewinska and colleagues 10 and from 7-fold to 18-fold lower than the LOD detected in previous studies. 7,9 In terms of precision, our assay ranges from 3.2% to 8%, similarly to the values previously observed (2.6–6.4%).…”
Section: Resultssupporting
confidence: 86%
“…To fill this gap, two recent independent studies developed a smartphone-assisted PAD for protein determination in human biological samples by comparing the analytical performance of the most common colorimetric assays available. 9,10 The results showed that the bromophenol blue (BPB) dye-binding method exhibited the best analytical performance and aligned with previous colorimetric PAD methods which have been developed. 5–8 In this assay, following the binding of BPB with proteins under acidic conditions (pH < 3), the colour of the substrate switches from yellow to green/blue, and the intensity of the colour developed is directly proportional to the protein concentration.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations